2012
DOI: 10.1042/bst20120015
|View full text |Cite
|
Sign up to set email alerts
|

The self-perpetuating tau truncation circle

Abstract: Pathological truncations of human brain proteins represent the common feature of many neurodegenerative disorders including AD (Alzheimer's disease), Parkinson's disease and Huntington's disease. Protein truncations significantly change the structure and function of these proteins and thus can engender their pathological metamorphosis. We have shown previously that truncated forms of tau protein are contained in the core of the paired helical filaments that represent the main constituent of neurofibrillary pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 57 publications
2
42
0
Order By: Relevance
“…Tau undergoes various post-translational modifications, hyperphosphorylation being the most prominent and studied changes [10]. Mounting evidence suggests that not only the hyperphosphorylation, but also tau cleavage plays an important role in the progression of AD [11, 12]. N- and C-terminal fragmentation induces toxic tau aggregation in N2a cells [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tau undergoes various post-translational modifications, hyperphosphorylation being the most prominent and studied changes [10]. Mounting evidence suggests that not only the hyperphosphorylation, but also tau cleavage plays an important role in the progression of AD [11, 12]. N- and C-terminal fragmentation induces toxic tau aggregation in N2a cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…When cleaved at Asp421 by caspase, tau assembles more rapidly and more extensively into tau filaments in vitro [14], suggesting that cleaved tau enhances polymerization kinetics and serves as a nucleation center, promoting the pathologic assembly of tau filaments [15, 16]. Caspases [11, 12, 17], the ubiquitin-proteasome system [18], and calpains [19, 20] are all implicated in tau cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…PHFs include hyperphosphorylated and truncated forms of Tau (4). The importance of a truncated form of Tau in disease progression has been underlined by the identification of various sizes of Tau species, ranging from 10 kDa to higher molecular mass, in aggregates of human AD brains (5). On the other hand, recent studies have demonstrated that injection of brain homogenates containing mutant Tau aggregates in the brain of transgenic mice expressing wild‐type human Tau can transmit Tau pathology, suggesting a prion‐like spread of Tau (6).…”
mentioning
confidence: 99%
“…It has been proposed that in disease conditions such as AD, rare species of toxic TAU exist that need to be removed in order to restore neuronal functions. Other possibilities include a role for non-coding RNAs including mi-RNAs and truncated forms of TAU in toxicity, as discussed elsewhere (Schonrock et al, 2010; Hebert et al, 2012; Zilka et al, 2012). As discussed here, simply reducing TAU levels may be therapeutically beneficial.…”
Section: Discussionmentioning
confidence: 99%